The role of audit quality in firm valuation: Evidence from an emerging capital market with a joint audit requirement. Issue 5 (12th September 2016) - Alfraih, Mishari M.
Abstract : Purpose: The purpose of this paper is to examine the effect of audit quality on the value relevance of earnings and book value. Because joint audit is mandated for all Kuwait Stock Exchange-listed firms, it is hypothesized that the higher the quality of the audit team (as measured by the number of Big 4 audit firms in the joint audit team), the higher the value relevance of earnings and book values for equity valuation. Design/methodology/approach: Consistent with prior research, the value relevance of earnings and book value is measured by the adjusted R 2 derived from theOhlson's 1995 regression model. The number of Big 4 audit firms represented on the firm's audit team is used as a proxy for audit quality. Three tiers of audit quality exist, namely, two non-Big 4 audit firms, one Big 4 and one non-Big 4 audit firms or two Big 4 audit firms. To address this paper's objective, the association between audit quality and the value relevance of earnings and book value were examined using four approaches. The final sample consists of 1, 836 firm-year observations and covers fiscal years from a 12-year period (2002-2013). Findings: Taken together, the four approaches used collectively provide empirical evidence that audit quality positively and significantly affects the value relevance of accounting measures to market participants. Importantly, the results reveal significant variations in the value relevance of earnings and book value jointly across the three possible auditor combinations. Research limitations/implications: Although using auditor size as a proxy for audit quality is well established in the auditing literature, a limitation of that proxy is that it measures audit quality dichotomously, which implicitly assumes a homogeneous level of audit quality within each group. Practical implications: The findings show the importance of high-quality and rigorous external audits in improving the value relevance of accounting information. Originality/value: This study contributes to the extent literature on audit quality by exploring the role of audit quality in a unique institutional setting that imposes mandatory joint audits. Although prior studies have investigated the effect of joint audit pair choice on earnings management and audit fee premium, this study is the first to investigate the effect of joint audit pair choice on the value relevance of accounting information.